The relationship between leadership development initiatives and leadership effectiveness among middle-level leaders in three Malaysian public institutions of higher education / Sakinah Muslim - Muslim, Sakinah (Institute of Graduate Studies, UiTM, 2018)
In a competitive world, higher education institution must move at the right pace in response to the fast changing global higher education landscape. No doubt, a world class higher education system need a world-class leadership. One important concept of the theory for this study is that transformational leaders can be developed. A large body of research related to leadership effectiveness and succession planning emphasised the importance of leadership development. This explores the potential relationship between leadership development initiatives and leadership effectiveness in higher education setting. The research questions addressed by this research include how significant experiential learning, developmental relationship, education and assessment has been in ensuring leadership effectiveness. It also explores the influence of senior leaders’ commitment in the relationship of leadership development initiatives with essential elements of leadership effectiveness in Malaysian public higher education institution…